Managing the Selection of Highly Competitive Interscholastic Sport Teams: Recommendations from Coaches on Cutting Players - Chad Seifried; Tim Casey (Journal of Applied Sports Management, 2013)
This work used a purposive sample of 15 coaches to record information on the cutting process of highly competitive interscholastic varsity boys’ basketball programs. Semi-structured interviews and a content analysis of organizational documents were used to create a basic philosophy on the cutting process. The themes discovered centered on the purpose of interscholastic sport and team selection preferences during the cutting process, methods to reduce the tryout field, and how to break the news to prospective student-athletes about their elimination. Overall, the researchers provide several different strategies suggested by coaches to cut student-athletes from sport teams which they advocate can be done with sensitivity and concern for the student’s welfare/mental condition and for the good of the winning-centered team. Furthermore, within the article, the researchers developed a selection matrix or framework with the help of the participants to help coaches identify important strengths and weaknesses of prospects during the tryout period.
Keywords: Externally Controlled Withdrawal; Tryouts; Interscholastic Sport